A Hallyu em Perspectiva Multidimensional: uma análise das Dimensões Acadêmica, Governamental e da Indústria Cultural - Carvalho, Fernanda Vieira (2024)
This dissertation introduces the Hallyu, a term created by the Chinese media in the late 90s and currently used to define the popularity of South Korean celebrities and cultural products. This phenomenon transmits Korean standards, behavioral codes, consumer preferences, fashion, cuisine and language. Considering the economic returns and promotion of improving national image, it has been explicitly adopted by South Korea since the 2000s, reinforcing the government's neoliberal economic agenda and cultural nationalism. In this regard, the research question is “what are the effects of Hallyu as an international cultural phenomenon?” The purpose is the analyze of repercussion of the phenomenon on three sectors (1) Academic, remarking its effects on Brazilian and South Korean academia; (2) Government, through the analysis of the South Korean government's involvement with Hallyu and its use as a political instrument (especially in South Korean cultural diplomacy); and in (3) Cultural Industry, introducing the development of this sector based on Hallyu and how cultural products develop images and disseminate imaginaries about South Korea. With the purpose of analyze the Hallyu from a multidimensional perspective, a bibliographical and documentary research was adopted, demonstrating the essentially qualitative nature of this study. To investigate the impact of the Korean Wave on the South Korean Academy, bibliographic research on the Web of Science platform was contrasted with studies by Hong, Park and Park (2017), Yoon and Kang (2017) and Hong et al. (2019). Subsequently, a bibliometric study was conducted on the Catálogo de Teses e Dissertações da Capes and articles available on the Web of Science and Google Scholar platforms to analyze the effects on the Brazilian Academy. The historical construction of government institutions and cultural industries involved in the Korean Wave was obtained through a literature review. Data on exports of Korean cultural products and analysis of the South Korean national image were obtained from websites and reports produced by the Ministry of Culture, Sports and Tourism, the Ministry of Foreign Affairs, the Korean Culture and Information Service (KOCIS), the Korea Creative Content Agency (KOCCA) and the Korea Foundation for International Cultural Exchange (KOFICE). As a result, in the academic aspect there is an impact on study topics and academic production in South Korea and Brazil. In the government sector, it was concluded that the Korean Wave was used as a South Korean public diplomacy mechanism and a state policy, explaining the institutional organization which for formulate and implement cultural policies. Finally, for the South Korean cultural industries, it was also found that the popularity of cultural products also depends on unique and peculiar factors in the consumers countries. Hallyu represents significant changes in the relationships of access, consumption, production and distribution of information, furthermore a redefinition of cultural identity for the international public.